Inverse cowgirl : a memoir - Weigel, Alicia Roth (HarperOne, an imprint of HarperCollins Publishers, 2023)
"From a celebrated activist on the forefront of fighting for intersex representation and rights-and a subject of the forthcoming documentary Every Body, from the filmmakers behind RBG-a funny, thought-provoking collection of essays about owning your identity and living your truth"--